Representing and commoning the refugee crisis: The 'assemblage' of the Lesvos Migration Atlas. Issue 1 (1st June 2019) - Tsilimpounidi, Myrto; Tselepi, Naya; Pangalos, Orestis; Petropoulou, Chryssanthi 'Christy'
This article uses a critical lens to examine the various representations of the so-called 'refugee crisis' in Lesvos, Greece through both the system of the hotspot regime and the performative acts of commoning, defined as the creation of the commons. It also proposes a process of commoning by the creation of an 'assemblage' of the Lesvos Migration Atlas. In this manner, the Atlas as an outcome of the research is itself a representation that embraces theory, narratives, practices, and acts; a visual and symbolic tool that provides space for photographic material, videos, artworks, (re)mappings, everyday stories, and reflective texts. At the same time, it is a collective process of capturing, writing and representing, open to new material and scripts ‐ thus a product in a process of becoming. Overall, the online and interactive Lesvos Migration Atlas can well be approached as an 'assemblage' that respects the mobility and contingency of the various crises, representations and acts of commoning. In the Atlas, the refugee crisis, the hotspot regime and the common spaces that have been created are brought together through the emergence and critical confrontation of the multiple representations of Lesvos.